PAKISTAN PSYCHIATRIC SOCIETY: A REFLECTION OF EARLY YEARS - Ahmed, Syed Haroon (Journal of Pakistan Psychiatric Society, 2023)
It is nostalgic to recall formative years of the society for the reason that we psychiatric met in different cities of West and the then East Pakistan (now BanglaDesh) to ponder and agree to set up this society. We should be grateful to the Pakistan Medical Association, our national and parent bowly because it was during its annual and biennial conferences that few of us psychiatrists first met to share our frustrations regarding the sate of mental health and psychiatric profession in At a time when our morale was at its lowest ebb and in an attempt to overcome our inhibitions, we, during one of the bigger ventures of Pakistan Medical Association, the joint meeting of Pakistan Medical Association and British Medical Association, met to discuss the possibility of organizing ourself. It was at the lawns of the Boat Club, on a sunny aftercon of a cold December, in 1966, that we used the hospitality of Dr. Afzal Habib. Besides the host, those present included the late Dr. G. A. Asghar, Dr. Zaki Hasan, Dr. H.A.G. Kazi. Dr. Iftikhar, Dr. Raihana Beg and the writer Dr. Farrukh Hashmi from U.K. also attended.